2022
DOI: 10.47391/jpma.3416
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of preterm neonates with patent ductus arteriosus: a retrospective review from a tertiary care hospital

Abstract: The management of patent ductus arteriosus (PDA) in preterm neonates remains controversial. A retrospective review was conducted to determine the outcomes in preterm neonates with PDA. Data of neonates admitted to the Aga Khan University Hospital from January 2012 to December 2016 were retrieved from patient records. Of the 208 neonates included in the study, 143 (68.7%) received no treatment, while 65 (31.2%) underwent pharmacotherapy and/or surgical ligation for PDA closure. PDA closure was spontaneous in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nonadherence to SMBG practice amongst type 1 diabetic patients was 40% where as it 48% in case of type 2 Diabetic patients. 19 This finding correlates well with observation done k.Khowja at all, Yaqoob at 14 all and Farhan at all. 20 They Also found that Nonadherence to SMBG practice was low than SMBG adherence practice.…”
Section: Discussionsupporting
confidence: 89%
“…Nonadherence to SMBG practice amongst type 1 diabetic patients was 40% where as it 48% in case of type 2 Diabetic patients. 19 This finding correlates well with observation done k.Khowja at all, Yaqoob at 14 all and Farhan at all. 20 They Also found that Nonadherence to SMBG practice was low than SMBG adherence practice.…”
Section: Discussionsupporting
confidence: 89%
“…It is consistent with a previous study that showed that feelings of social exclusion and embarrassment influence diabetes mellitus self-management practices (18) . Cultural norms and the unaffordability of certain medications, and an unhealthy diet impede healthy eating practices in Pakistani culture (19) . The present study echoes the finding of a study showing that diabetic patients eat whatever is cooked at home (20) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mortality rate associated with tetanus remained high, indicating a need for improved management and prevention efforts. Similarly, Khowaja & Qureshi (2011) in their study of tetanus cases at a tertiary care hospital in Pakistan found that over five years (2011)(2012)(2013)(2014)(2015), the majority of cases were in males, and the highest incidence was in the age group 15-24 years. The study also found a high mortality rate (50%) among tetanus cases, highlighting the need for timely and appropriate management.…”
Section: Introductionmentioning
confidence: 93%
“…This can be achieved by maintaining proper wound care, including cleaning, and dressing any injuries, and by being vaccinated with the tetanus vaccine. Khowaja & Qureshi (2011) assert that Tetanus toxoid is a chemically modified version of the tetanus toxin that has been inactivated or "killed" allowing it to be used as a vaccine for protection against tetanus without causing illness. When injected into the body, the tetanus toxoid stimulates the immune system to produce antibodies that can recognize and protect against the tetanus toxin in the event of exposure to the bacteria.…”
Section: Introductionmentioning
confidence: 99%